Avaliação de ecótipos de figueira-da-índia [Opuntia ficus-indica L. (Miller)] para produção de fruto - Reis, C.M.G. (2017)
Avaliação de ecótipos de figueira-da-índia [Opuntia ficus-indica L. (Miller)] para produção de fruto